A look at the other devices in the Foreign Language Training: Isomorphisms of Language Policy and the Mediation - Yurén, Teresa; Saenger, Cony (Education Policy Analysis Archives, 2006)
"The look of the other in the devices of foreign languages formation. Isomorphisms of linguistic policy and mediation". The case of the bachelor degrees for French teachers in Mexico is analyzed in order to show how the ways of looking at the other and be looked by the other can impact the mediation types and the treatment of the cultural distances, which in turn rebounds in the appropriation of the foreign language, the configuration of the professional ethos and the acquisition of competences for self-formation. Qualitative data were obtained by means of interviews, observations and collection of documents and the work was done by combining structural analysis, representation analysis, analysis of identity, genealogy and political discourse analysis. As epistemological focus, the reconstruction of the formation device was adopted, highlighting the ethical-political dimension. After analyzing the representations of the teachers on their task and their activity as mediators, as well as their social and cultural identifications, five mediation types and four treatment forms of alterity were identified: the plotted alterity, the confiscated alterity, the aculturing opening and the polyvalent opening. It was found that these forms of looking at the other are also present in the field of educational and cultural cooperation between the countries involved, as well as in the strategies and policies of use and dissemination of the language deployed in the history of said countries. The conclusion is that only a non-confiscating look with polyvalent opening can contribute to the appropriation of the target language, the conformation of an autonomous professional ethos and the acquisition of dispositions for self-formation.